Hubungan Stigma dengan Tingkat Kepatuhan Pasien dalam Pengobatan TBC di Rumah Sakit Umum Bhakti Asih Ciledug Tahun 2024 - Khaerul Anwar; Ekberth Mandaku; Tanto Tanto; Nurdewi Sulymbona (Pusat Riset dan Inovasi Nasional, 2024)
TB is an infectious disease caused by infection with the bacteria Mycobacterium Tuberculosis which can attack the lungs. However, it is not automatically transmitted because transmission depends on several factors such as: body resistance, air circulation conditions, ventilation and contact with people with TB. Based on hospital data in 2024 in the last 3 months, there were 317 cases of pulmonary TB, with 176 cases of patients diagnosed with TB. Treatment can be effective if patients comply with the rules for using drugs prescribed by doctors and from the results of the analysis there is a significant relationship between compliance with taking medication and the rate of recovery of tuberculosis patients. This figure is the third largest case of the disease after type 2 Diabetes Mellitus and Hypertension that occurred at Bhakti Asih Hospital. The purpose of the study was to determine the relationship between stigma and the level of patient compliance in TB treatment at Bhakti Asih Hospital, Ciledug. The research method used was Random Sampling with a sample size of 44 respondents and a measurement method using a questionnaire. The results of the analysis using the chi-square test showed that there was a significant relationship between stigma and compliance with taking pulmonary tuberculosis medication in lung patients at Bhakti Asih Hospital.